A seamless producer mobility management model for named data networks - Abrar, Ahmad (2025)
Named Data Networking (NDN) is an Information-Centric Networking (ICN) architecture designed to support content source mobility. While it efficiently handles consumer mobility through content caching, producer mobility remains a challenge. When a producer relocates, NDN routers still direct requests to the original location, causing Interest packet loss, high signalling overhead, and increased handoff latency. These issues degrade network performance and throughput, highlighting a gap in NDN’s mobility management. This study explores efficient solutions to enhance producer mobility, ensuring seamless and optimized content delivery in dynamic networks. Therefore, this research aims to propose a Producer Mobility Management Model (PMMM) to handles the associated producer mobility challenges and provides the optimal path. The PMMM incorporates mobility management packets, including the Mobility Notification Packet (MNP) and the Mobility Update Packet (MUP), and modifies standard forwarding processes to support these mobility management packets effectively. The MNP is used to inform the network and consumers about producer mobility, helping to reduce excessive packet loss and high signalling costs. Meanwhile, the MUP updates the producer's location within the network, notifies consumers of the producer's availability, and establishes an optimal communication path. A series of experiments confirm that PMMM improves network performance by reducing handoff latency, signalling costs, and packet loss, while enhancing path optimization and throughput. Compared to IBM, PMSS, and KITE, PMMM reduces handoff latency by up to 24%, ensuring smoother transitions when producers relocate. It also lowers signalling costs by up to 31%, reducing network overhead. Additionally, path optimization improves by 25%, leading to more efficient data routing. Packet loss decreases by 44% compared to KITE and 32% compared to PMSS, ensuring reliable data delivery. Finally, PMMM increases throughput by 17% over KITE and 12% over PMSS, improving network stability. These findings demonstrate that PMMM effectively addresses mobility challenges in NDN. This significant improvement highlights the PMMM's immense potential for future deployment, especially in the context of advanced technologies such as the Internet of Things (IoT), the Internet of Medical Things (IoMT), and sixth-generation (6G) mobile networks